International Redistribution of Income - Bourguignon, Francois; Levin, Victoria; Rosenblatt, David (2012)
How do international policies on aid, trade, and factor movements affect the international distribution of income? We calculate the impact by world decile of the actual level of aid flows and the effect on income of merchandise trade restrictions by high-income countries. We find that aid's distributional impact is equality enhancing, extremely small in terms of changes in inequality measures, but of some importance for the lowest decile of the distribution. We also find that some of this impact is counteracted by lost potential income in the lower deciles from merchandise trade barriers imposed by high-income countries.